1995
DOI: 10.1116/1.579599
|View full text |Cite
|
Sign up to set email alerts
|

ReSi2 thin-film infrared detectors

Abstract: Two types of thin-film infrared-sensing devices have been investigated using the narrow band-gap semiconductor, rhenium disilicide ͑E g ϳ0.1 eV͒. These are the ReSi 2 /n-Si heterojunction internal photoemission ͑HIP͒ detector and the ReSi 2 thin-film photoconductor. The HIP device was found to be rectifying and to obey a Fowler-type law with a long-wavelength cutoff of ϳ2.1 m ͑0.59 eV͒ at room temperature. In hopes of approaching the fundamental limit for a ReSi 2 -based photonic detector, ϳ12 m ͑0.1 eV͒, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Semiconducting transition-metal silicides such as CrSi 2 and FeSi 2 have also been regarded as nice thermoelectrics but it is generally believed that further improvement in thermoelectric properties is badly needed for these disilicides to be widely used [2]. Although a disilicide formed with Re is know to be a semiconductor, a little is known about its crystal structure and thermoelectric properties [3]. Early investigations found that the disilicide had a body-centered tetragonal C11 b (MoSi 2 -type, space group I4/mmm) structure with lattice parameters a=0.3132 nm and c=0.7681 nm [4].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconducting transition-metal silicides such as CrSi 2 and FeSi 2 have also been regarded as nice thermoelectrics but it is generally believed that further improvement in thermoelectric properties is badly needed for these disilicides to be widely used [2]. Although a disilicide formed with Re is know to be a semiconductor, a little is known about its crystal structure and thermoelectric properties [3]. Early investigations found that the disilicide had a body-centered tetragonal C11 b (MoSi 2 -type, space group I4/mmm) structure with lattice parameters a=0.3132 nm and c=0.7681 nm [4].…”
Section: Introductionmentioning
confidence: 99%
“…come from anisotropy in the electronic structure due to its rather complicated crystal structure as well as from a complex microstructure. (5) Although the value of Seebeck coefficient along [100] is moderately high (150-200 µV/K), it is very high along [001] (250-300 µV/K). The value of thermal conductivity is rather isotropic and reasonably small.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…A silicide formed with Re is one of those transition-metal silicides. Although a disilicide formed with Re is known to be a semiconductor, a little is known about its crystal structure and thermoelectric properties [5]. Early investigations found that the disilicide had a body-centered tetragonal C11 b (MoSi 2 -type, space group I4/mmm) structure with lattice parameters a=0.3132 nm and c=0.7681 nm [6].…”
Section: Introductionmentioning
confidence: 99%
“…The narrow band gap of -0.15 eV offers the potential of developing ReSi2.X-basedlong wavelength infrared detection devices [13]. The potential of tuning the band gap by alloying with Mo and epitaxial growth on Si [14] make this semiconducting silicide even more promising for infrared detector applications.…”
Section: Fig 1 Unit Cell Of Mosizmentioning
confidence: 99%
“…The potential of tuning the band gap by alloying with Mo and epitaxial growth on Si [14] make this semiconducting silicide even more promising for infrared detector applications. In particular, epitaxial ReSiz.X films on Si allow devices where the detector element and the signal processing circuitry can be integrated on one Si chip, a feature not possible in HgCdTe-based detectors [13]. A detailed characterization, using TEM, of the microstructure of epitaxial ReSiz.Xfilms on Si has not been performed.…”
Section: Fig 1 Unit Cell Of Mosizmentioning
confidence: 99%